Are Commodity Prices Leading Indicators of OECD Prices? - Durand, Martine (OECD Publishing, 1988)
This paper examines the hypothesis that commodity price trends are useful indicators of OECD price developments. After a discussion of statistical techniques to assess the time series properties of individual price indices, integration and cointegration tests are conducted on a wide set of individual and aggregate commodity price indices and consumer price indices for the major seven OECD countries. The results of the analysis suggest that there is no clear evidence of any equilibrium relationship between levels of consumer and commodity prices. But relations between changes in a number of commodity prices such as metals and agricultural raw material prices and consumer prices may be established. The stability over time of such relationships is also tested ...
Keywords: Economics